Efikasi Penggunaan Video Live dalam Pembelajaran Daring: Analisis Performa Mahasiswa pada Kelas Kontra Bas - Riyan Hidayatullah; Prisma Tejapermana; Rangga Firdaus; Fajar Riyantika; Septiana Wahyuningsih (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2025)
Purpose: This study aims to examine student self-efficacy in the use of "live video" in learning counter bass in the Music Education Study Program (PSPM), Faculty of Teacher Training and Education (FKIP), University of Lampung (Unila). In recent years, there has been a growing interest among academics and practitioners in exploring the factors that contribute to students' declining awareness of learning music, including students' self-efficacy in selfpractice of musical instruments, as traditional self-practice without supervision is no longer effective, so teachers are looking for ways to optimize it using technology. Methods: The qualitative research method used was observations and unstructured interviews of doublebass class students and qualitative interviews to explore their perceptions. Students engaged in video learning for one semester, where video sessions were used for performance demonstrations and independent practice. Each development was observed in weekly live meetings, and progress videos were collected. Results and Discussion: The results illustrate that using "live video" as a stimulus for students' self-efficacy in understanding counter bass techniques and learning stages had a significant impact. In addition, the quality of the interactive process of practising the instrument independently promoted confidence and understanding of performance details. Conclusion: "live video" supports the emergence of efficacy in the double-bass learning experience. At the same time, it also requires further infrastructure development and training for its optimization. The implications of this study point towards online learning as a means to fulfill the needs of self-directed learning through platforms, while still considering the aspect of student engagement.